Professional standard of care and sharing economy - NETO, Renato (Revista Jurídica Portucalense, 2023)
Many new legal relations were fashioned in the collaborative economy arena. Some of them are characterized by entirely new elements, but some of them are very similar to existing legal transactions and activities that are already regulated. These new situations are qualified mainly for goods and services exchange between “peers”. Several of these new affairs are based on services provisions situated in legal grey areas, lacking consumers, clients and providers protection. It is important to outline the standard of care expected from the providers to properly address the issue regarding these services, especially to define parties’ obligations. The paper drafts a concept of professionalism, to establish a basis for assessing whether it is possible to demand a professional standard of care in a peer-to-peer service, which would be qualified and higher than ordinary diligence. In particular, the homestay services regulation in Portuguese Law is analysed, with the aim to evaluate if these sharing economy activities tend to be professionalized. Lastly, it is considered what is the standard of care to be expected.